2013
DOI: 10.1002/ccd.22650
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous “High Take‐Off” of the right coronary artery evaluated by coronary CT angiography

Abstract: Congenital coronary anomalies are uncommon but can cause sudden cardiac death or myocardial ischemia. Conventional coronary angiography is an invasive and expensive modality, sometimes unable to delineate the exact origin and course of an anomalous artery. In this case report, we describe an "extremely rare" anomaly of the right coronary artery where a 64-slice multidetector computed tomography provided valuable information regarding its exact site of the aortocoronary take-off and its spatial relationship wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A similar procedure was adopted by Jim et al 11 Occasionally, an AORCA may be associated with an inter-arterial or intramural course, which can be well documented by 3D-CT angiogram. 12,13 This was however, not required in our cases.…”
Section: Discussionmentioning
confidence: 68%
“…A similar procedure was adopted by Jim et al 11 Occasionally, an AORCA may be associated with an inter-arterial or intramural course, which can be well documented by 3D-CT angiogram. 12,13 This was however, not required in our cases.…”
Section: Discussionmentioning
confidence: 68%
“…3D-CT angiogram is an alternative and superior imaging tool to look into the AORCA with unresolved issues like interarterial course or intramural course. 16,17 In our study, computerized tomography (CT) of aortic root angiogram was done in 2 cases originating from right coronary sinus to exactly locate the aberrant ostia location after initial failure to hook during PCI, and retrospectively in cases of contralateral origin to rule out a malignant course. The four most common coronary anomalies that need mention are 1) The circumflex artery originating from the right coronary artery (RCA) or in the right coronary sinus; 2) RCA arising anteriorly with high take-off, 3) the left main artery originating from the right coronary sinus and in 25% cases it takes interarterial course and 4) a separate origin of the left anterior descending and circumflex coronary arteries called short left main artery.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest performing multi-detector computed tomography (MDCT) for accurate diagnosis, especially in adult patients. [ 10 ] However, for a pediatric patient who presents with no symptoms related to high take-off RCAs, the adverse effects of radiation exposure outweigh the benefits of MDCT in this setting. In this case, although it was missed preoperatively under echocardiogram, we showed that it was feasible to demonstrate the origin and course of an anomalous coronary artery under echocardiography.…”
Section: Discussionmentioning
confidence: 99%